The ALMA Survey of Gas Evolution of PROtoplanetary Disks (AGE-PRO). VIII. The Impact of External Photoevaporation on Disk Masses and Radii in Upper Scorpius - Rossella Anania; Giovanni P. Rosotti; Matías Gárate; Paola Pinilla; Miguel Vioque; Leon Trapman; John Carpenter; Ke Zhang; Ilaria Pascucci; Lucas A. Cieza; Anibal Sierra; Nicolas T. Kurtovic; et al. (The Astrophysical Journal, 2025)
Protoplanetary disk evolution can be deeply influenced by the UV radiation emitted by neighboring massive stars (mainly of spectral types O and B). We show that the process of external photoevaporation , which causes an outside-in depletion of disk material due to environmental UV radiation, can lead to a significant decrease in disk size, disk mass, and lifetime even at moderate irradiation levels (1–10 G _0 ). In this work, we investigate the role of external photoevaporation in shaping the masses and sizes of the 10 AGE-PRO disks in the Upper Scorpius (Upper Sco) region, which we estimate to be subject to far-ultraviolet (FUV) fluxes ranging between ∼2 and ∼12 G _0 , on average. We compare the disk masses and sizes resulting from 1D numerical viscous evolution simulations, in which the effect of external photoevaporation is included, to the values retrieved from the AGE-PRO observations. While the pure viscous framework fails in adequately explaining the observed disk properties in Upper Sco, with the inclusion of external photoevaporation, we can successfully reproduce gas disk sizes for seven out of 10 sources within a factor <2, when the initial disk mass is 1%–10% of the stellar mass. We emphasize the importance of accounting for the environmental irradiation when comparing star-forming regions of different ages, even when moderate FUV irradiation fields are experienced, as in the case of Upper Sco.